2018
DOI: 10.1159/000495201
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Mosaic Karyotype of 45,X/46,X,psu idic(Y)(p11.32)/46,XY with <b><i>SHOX</i></b> Haploinsufficiency, External Male Genitalia, and Short Stature

Abstract: In this case study, we describe a 3-year-old boy who was referred to the Inonu University Hospital with short stature complaint. His height was 86 cm (-2.96 SDS), weight was 12 kg (-2.43 SDS), and head circumference was 46.5 cm (-2.34 SDS). Chromosomal analyses were performed on cultured peripheral blood lymphocytes of the patient and his parents and showed the patient's karyotype mos 45,X[20]/46,X,idic(Y)(p11.32)[29]/46,XY[1]. The karyotypes of the parents were normal. Subsequently, specific FISH probes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…However, some researchers reported that a patient without AZF deletions demonstrated azoospermia possibly due to other Y chromosome structural abnormalities or mosaicism [54]. Yp11.32 also contains the short stature homeobox (SHOX) gene, which participates in the proliferation and differentiation of chondrocytes [55] and hence growth retardation in affected patients. Some patients showed features of Klinefelter syndrome resulting from extra Y chromosome material [31, 56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers reported that a patient without AZF deletions demonstrated azoospermia possibly due to other Y chromosome structural abnormalities or mosaicism [54]. Yp11.32 also contains the short stature homeobox (SHOX) gene, which participates in the proliferation and differentiation of chondrocytes [55] and hence growth retardation in affected patients. Some patients showed features of Klinefelter syndrome resulting from extra Y chromosome material [31, 56, 57].…”
Section: Discussionmentioning
confidence: 99%